PARKIR BERLANGGANAN DI KABUPATEN SIDOARJO (Studi Interaksi Simbolik Parkir Berlangganan di Kabupaten Sidoarjo) - Doni Rudiyanto; Didik Hariyanto (Universitas Muhammadiyah Sidoarjo, 2015)
The purpose of this study to explain the meaning of symbolic interaction behaviors is used parking attendants to collect of illegal parking fees subscribe. This type of research was qualitative research. Data collection techniques is obtained through interviews, observation, and documentation. The results study showed that the activities is done by illegal parking officer are: illegal parking officer coordinate with official parking officer, many symbols irregularities (regulated by transportation department) by official parking attendants or illegal parking attendants, as well as services provided to customers like cardboard availability on the vehicle and helps to move customer vehicles. While the behavior is shown subscribe parking do not understand the card should be the right of customers and keep paying parking fees.